(untitled) (The Pakistan Development Review, 1995)
As witnessed by Mexico and Argentina in 1995 and by the Southern Cone countries of Latin America in the early 1980s, the macroeconomic adjustment to a sudden reversal of foreign capital flows can be extremely painful. There are at least four major reasons why governments and central banks should care about the sustainability of the capital flows which their economies can tap abroad: • First, international capital markets are highly imperfect due to enforcement problems and information asymmetries. Trade in financial assets, unlike trade in goods, is incomplete and intertemporal, based on promises to pay in the future. The time lag between financial transaction and contract completion, coupled with incomplete insurance markets and other distortions, can generate abrupt and destabilising market corrections. Financial markets often do not discipline the recipient countries when the latter do not face an upward supply curve for foreign capital but rather face a horizontal supply curve due to currency appreciation and falling spreads charged by lenders, until capital rationing sets in [Devlin et al. (1994)] . • Second, any shortfall in capital inflows will require immediate cutbacks in domestic absorption to restore external balance. The savings-investment balance is more likely to be achieved through cuts in investment than through higher savings in the short term, compromising future output levels. Current output levels fall to the extent that rigidities prevent resource reallocation [Devlin et al. (1994)], so that contractionary disabsorption effects outweigh expansionary substitution effects.